Ripple voltage and its elimination in low voltage power supply - Torla, Ahmad Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Gani (2012)
This paper shows the simulation results of the effects of phase difference on the output ripple voltage of a low voltage power supply circuit. The circuit uses a rectifier circuit which adds the squares of two out-of-phase sine waves. The circuit focuses on the constraint of rectifying a low voltage input AC source while analyzing the ripple voltage in the output and is designed in such a way that the phase difference can be determined by varying only discrete values of a resistor and capacitor. The simulation is operated with a 100mV input sine wave with an output of 1.622 V DC is obtained. The ripple voltage varies from 732 μV to 434 μV for a phase difference ranging from 97.33° to 82.34° with its minimum ripple at 90°.